Linking air pollution appraisal to EFL teachers' negative emotion via mental effort: the moderating role of working memory capacity - Shi, Yijun; Wang, Shuhua; Hao, Qi (Frontiers in Psychology, 2025)
Based on Cognitive Load Theory, this study developed a moderated mediation model to examine the relationship between English as foreign language (EFL) teachers' air pollution appraisal and negative emotions. Specifically, it hypothesizes that air pollution appraisal significantly increases the mental effort of EFL teachers, which in turn leads to the manifestation of negative emotions. Additionally, the study introduces the concept that the working memory capacity of EFL teachers can negatively moderate the impact of increased mental effort on their emotions, effectively attenuating the overall mediating effect. Data for this research was gathered from daily diary surveys of 182 EFL teachers across 23 high schools in Shanxi Province, China. The hypotheses were tested using two-level Hierarchical Linear Modeling and Monte Carlo analysis, with all proposed hypotheses receiving empirical support. This study significantly enriches the existing literature on air pollution appraisal, EFL teacher emotion, and Cognitive Load Theory, offering crucial practical insights for educational institutions on how to mitigate the adverse effects of air pollution on teachers.